Does Adoption of Improved Variety Encourage Farmers to Invest in Modern Inputs and Use Good Practices? Evidence from Rice Farmers in Guinea - Arouna, A.; Barry, M.L.; Kamano, P.; Yabi, J.A. (Cambridge University Press, 2024)
Iron toxicity is one of the constraints limiting rice production in Africa. This study used a randomized controlled trial to assess the impact of an iron toxicity-tolerant variety, named ARICA 6, on different outcomes and investment in modern inputs by smallholder farmers. Two rounds of data were collected from 520 rice-farming households in Guinea. Results showed that the use of ARICA 6 increased rice yield by 330 kg ha−1 and net income by US$ 120 ha−1 . However, adoption of improved variety may not be enough to crowd in investment in modern inputs because farmers face other constraints.